Extension and renovation of Oskar Reinhart Collection Am Römerholz : Winterhur, Switzerland 1993-1998 (A+U, 1999)
Extensión y renovación entre los años 1993 y 1998, del Museo Oskar Reinhart en Winterhur en Suiza.